2020
DOI: 10.1016/j.rse.2020.112031
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of marine atmospheric boundary layer roll detection using Sentinel-1 SAR data

Abstract: The ability of high-resolution synthetic aperture radar (SAR) to detect marine atmospheric boundary layer (MABL) roll-induced roughness modulation of the sea surface wave field is well known. This study presents SAR measurements of MABL rolls using global coverage data collected by the European Space Agency's C-band Sentinel-1A satellite in 2016-2017. An automated classifier is used to identify likely roll events from more than 1.3 million images that were acquired at two incidence angles of 23° and 36.5° in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…Wind rows are detected mostly in the case of light-moderate wind speed regimes (i.e., W less than 13.8 m/s) and along-shore winds (Figure 17a,b, respectively). This finding confirms the results in References [20,21], where it is reported that wind rows are most commonly observed at wind speeds near 8-9 m/s. Whatever the wind speed and direction, the Low-and the Medium-Scale selections occur more frequently than the High-Scale one.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Wind rows are detected mostly in the case of light-moderate wind speed regimes (i.e., W less than 13.8 m/s) and along-shore winds (Figure 17a,b, respectively). This finding confirms the results in References [20,21], where it is reported that wind rows are most commonly observed at wind speeds near 8-9 m/s. Whatever the wind speed and direction, the Low-and the Medium-Scale selections occur more frequently than the High-Scale one.…”
supporting
confidence: 93%
“…The developed algorithms basically rely upon the estimation of the prevailing local orientation of linear wind induced and aligned SAR signatures, such as those from Boundary Layer Rolls (BLRs) and Wind Streaks (WSs) [18,19]. These features, otherwise termed "wind rows", could be visible on SAR amplitude in favorable conditions, which are determined by thermal and dynamic air-sea instability and typical wind speed values from 2 m/s, with the highest probability of wind streaks in the SAR images found for wind speeds of about 8-9 m/s [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The dual-polarization filter is hopefully applied on other C-band satellite data, i.e., RADARSAT-2, yet the incidence angle differing from Sentinel-1 might gave slightly different performance. The encouraging performance of a dual-polarization filter to detect rain signatures in SAR images seems to be applicable also to other, non-rain-related features visible on SAR images, such as roll vortices [2]. Additionally, in the particular case of rain detection and segmentation, further work could be done to decipher between the various rain contributions (i.e., stratiform rain, convective rain) and the possible relationship of backscattered signal with lighting events by exploiting the full capability of SAR (for instance, by including phase information), including data from ground-based radars but also other ancillary products such as the Geostationary Global Lightning Mapper (GLM).…”
Section: Discussionmentioning
confidence: 95%
“…Copernicus level-2 ocean products encompasses waves (OSW), wind (OWI) and radial surface velocities (RVL) measurements. However, many other ocean and atmospheric geophysical phenomena such as oceanic front, convective cells, modulation of the stress in the marine atmospheric boundary layer or rain [1,2] also affect the signal. Although routinely available since the Radarsat-2 mission, the use of dual-polarization measurements for ocean processes analysis and level-2 ocean product definition is still emerging.…”
Section: Introductionmentioning
confidence: 99%
“…It was later supplemented by another 10,000 images. In [14], deep learning models trained from this dataset led to promising results with an excellent classification performance [15]. However, this effort could not generalize to imagettes with at least two phenomena, and, as a categorization task, is inherently limited in resolution.…”
Section: Introductionmentioning
confidence: 99%